A DEVELOPMENT OF LEARING ACTIVITIES BY USING TASK-BASED LEARNING AND AUTHENTIC LEARNING TO ENHENCE LISTENING ABILITY AND SPEAKING ABILITY IN MYANMAR LANGUAGE FOR GRADE 10 STUDENTS - Krisathian, Sopit; Thamrongsotthisakul , Wichian (Journal of Buddhist Education and Research (JBER), 2022)
This independent study aims to (1) create and find the efficiency of the development of learning activities by using task-based learning and authentic learning activities in order to enhance Myanmar Language listening and speaking ability for Grade 10 students based on the criterion 75/75 and (2) try using the development of learning activities by using task-based learning and authentic learning activities. The study has been conducted by 2 steps research methodology and development. A sample group was twenty–five Grade 10 students who were studying at Phadungpanya School, Tak Province that were chosen by Cluster sampling. The research instrument is task-base leaning and authentic learning activities in order to enhance Myanmar Language listening and speaking ability. The data were analyzed by using mean, standard deviation, and t-test dependent. The results revealed that: The task-base leaning and authentic learning activities in order to enhance Myanmar Language listening and speaking ability for grade 10 students had the efficiency (E1/E2) at 77.67/78.52 which mean it met the criterion 75/75. The comparison of Myanmar Language listening ability during studying and after studying that using task-based learning and authentic learning activities. The pre-test scored an average at 8.76 points. The post-test scored an average at 15.44 points. The average scores analyzed by using t-test Dependent Samples found that “t” valued at 23.76. It could be concluded that the average scores after studying were significantly higher than those before studying at .05. The comparison of Myanmar Language speaking ability during studying and after studying. The pre-test scored an average at 8.92 points. The post-test scored an average at 13.64 points. The average scores analyzed by using t-test Dependent Samples found that “t” valued at 13.17 and Sig at 0.0000. It could be concluded that the average scores after studying were significantly higher than those before studying at .05.